Philosophy of Prediction and Capitalism - Frings, M.S. author. aut Link
IX, 149 p.
Keywords: There is little more than a decade left before the bells allover the world will be ringing in the first hour of the twenty-first century, which will surely be an era of highly advanced technology. Looking back on the century that we live in, one can realize that generations of people who have already lived in it for the better parts of their lives have begun to ask the same question that also every individual person thinks about when he is faced with the first signs of the end of his life. It is the question: "Why did everything in my life happen the way it did?" Or, "It would have been so easy to have channelled events into directions other than the way they went. " Or, "Why, in all the world, is my life coming to an end as it does, or, why must all of us face this kind of end of our century?" Whenever human beings take retrospective views of their lives and times - when they are faced with their own personal "fin du siecle" - there appears to be an increasing anxiety throughout the masses asso ciated with a somber feeling of pessimism, which may even be mixed with a slight degree of fatalism. There is quite another feeling with those persons who were born late in this century and who did not share all the events the older generation experi enced.